(untitled) (The Journal of Economic Concerns, 2024)
This research investigates the impact of motivational factors on employee performance within the Nepalese banking industry, a sector critical for the nation’s financial stability and economic growth. Recent growth in Nepal’s banking sector, driven by factors such as increased financial inclusion and technological advancements, underscores the need for a highly motivated and productive workforce. Employee performance, defined as the measurable contribution of an individual to organizational goals, is crucial for maintaining a competitive edge. This study explores the relationship between motivation and performance, drawing on need-based theories, goal-setting theory, and social cognitive theory, while considering Nepal’s unique socio-cultural context. This study investigates the impact of intrinsic and extrinsic motivational factors on employee performance within the banking sector in Nepal. Data were collected from 350 respondents across various banks through online surveys, with a pilot test conducted to ensure clarity and reliability. The survey assessed both types of motivational factors and their influence on employee performance. Demographic analysis provided key insights into the participant pool, enhancing the understanding of the sample’s characteristics. The findings underscore the importance of both intrinsic factors, such as job satisfaction and professional development, and extrinsic factors, including competitive salaries and job security, as key motivators for employee performance. Additionally, the study highlights the influence of cultural values, such as collectivism and respect for hierarchy, in shaping employee motivation in Nepal. By employing a descriptive research design and rigorous methodological steps, including statistical analysis using SPSS, this study provides a comprehensive understanding of the motivational landscape in Nepal’s banking sector. The insights gained can guide banks in developing effective strategies to enhance employee motivation and performance, contributing to the overall success and growth of the industry.